The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1985
DOI: 10.1029/ja090ia12p12183
|View full text |Cite
|
Sign up to set email alerts
|

A new type of VLF emission triggered at low altitude in the subauroral region by Siple Station VLF transmitter signals

Abstract: VLF wave data from the ISIS 2 satellite has revealed the existence of a new phenomenon in which coherent VLF signals from the Siple Station, Antarctica, VLF transmitter are observed to trigger a new type of VLF emission as these signals propagate upward to the satellite at 1400 km altitude through the ionosphere and low‐altitude magnetosphere. The emissions have the form of band‐limited impulses of approximately 20–30 ms duration. The bandwidth of the emissions is as much as 1 kHz and their amplitude is as muc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1987
1987
2014
2014

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 33 publications
(19 reference statements)
0
1
0
Order By: Relevance
“…The first suggestion that electrons could be lost from the radiation belts via cyclotron-resonant interactions was (remarkably) accompanied by a prediction that the same population could be artificially removed with radio wave transmitters; If…the failure of whistlers to remove the trapped radiation…is due to lack of power…it may be asked whether man-made transmitters can do better [Dungey, 1963]. Numerous studies have since suggested mechanisms to carry out this process-namely the artificial reduction of damaging fluxes of energetic electrons [e.g., Bell et al, 1985;Inan et al, 1985;Abel and Thorne, 1998;Rodger et al, 2006].…”
Section: Introductionmentioning
confidence: 99%
“…The first suggestion that electrons could be lost from the radiation belts via cyclotron-resonant interactions was (remarkably) accompanied by a prediction that the same population could be artificially removed with radio wave transmitters; If…the failure of whistlers to remove the trapped radiation…is due to lack of power…it may be asked whether man-made transmitters can do better [Dungey, 1963]. Numerous studies have since suggested mechanisms to carry out this process-namely the artificial reduction of damaging fluxes of energetic electrons [e.g., Bell et al, 1985;Inan et al, 1985;Abel and Thorne, 1998;Rodger et al, 2006].…”
Section: Introductionmentioning
confidence: 99%